Analisa Air Sungai Cibanten sebagai Sumber Air Baku Perusahaan Daerah Air Minum - Ade Ariesmayana; Frebhika Sri Puji Pangesti; Bahrudin Hawari Irsyadu Sabil (Jurnal Serambi Engineering, 2022)
Determining the source of raw water at a Regional Drinking Water Company is the first step in determining the location or place to fulfill raw water for clean water treatment purposes. One alternative that can be used as a source of raw water is river water. The purpose of this study is for initial analysis of a water source to be used as an alternative source of raw water for clean water treatment. In determining the selection of source water, there are 3 parameters that must be met for a water source, namely: Quantity, Continuity, and Quality. This research uses a quantitative analysis method in the form of field data measurements of population and population growth projections in the distribution area, by analyzing the quality test of the Cibanten River. Based on the results of data processing, the total average clean water needs of Serang District and Kasemen District is 697.06 liters/second, the water discharge capacity of the Cibanten River in 2020 has an average of 3,690 liters/second so that the Cibanten river discharge is suitable as a source of raw water. for the quantity and continuity parameters. For testing the water quality of the Cibanten River with parameters BOD, COD, TSS, TDS and pH, the value of the content of TDS and pH meets the environmental quality standards, for the values of TSS, TDS and BOD the results exceed the environmental quality standards. It needs to be treated first before being used as clean water and drinking water.